Long term follow up of recurrent uterine cervical cancer: A Case Report - Fatemeh Homaee Shandiz; Soodabeh ShahidSales; Parvaneh Dehghan (Mashhad University of Medical Sciences, 2014)
Background and Aim: Carcinoma of the uterine cervix is a significant cause of mortality because of malignancy in women. Radiotherapy is a major treatment modality for invasive cervical cancer with good treatment outcome in early-stage patients. However, substantial treatment failures still occur in the advanced-stage patients. In this case report a long term follow up of a 58 years old woman with stage II cervical squamous cell carcinoma (SCC), who was considered inoperable due to her general condition, cardiac poor function and ischemic heart disease (IHD) has been reported. After full dose external radiotherapy the patient became disease free till 6 years and after local recurrence, she was treated successfully with total abdominal hysterectomy (TAH) and bilateral salpingo-oophorectomy (BSO) as well as adjuvant chemotherapy with favorable results during a long term follow up of 14 years. It is concluded that long term favorable outcome may be achieved by intensive radiotherapy of uterine cervix SCC and probable recurrence could be managed successfully by surgical excision.